Amoxicillin‐loaded electrospun nanocomposite membranes for dental applications. Issue 5 (9th February 2016) - Furtos, Gabriel; Rivero, Guadalupe; Rapuntean, Sorin; Abraham, Gustavo A.
Abstract: Electrospun nanocomposite matrices based on poly(ε‐caprolactone) (PCL), nano‐hydroxyapatite (nHAp) and amoxicillin (AMX) were designed and investigated for dental applications. nHAp provides good biocompatibility, bioactivity, osteoconductivity, and osteoinductivity properties, and AMX, as antibiotic model, controls and/or reduces bacterial contamination of periodontal defects while enhancing tissue regeneration. A series of polymeric nanocomposites was obtained by varying both the antibiotic and nHAp contents. Fibrous membranes of different compositions were obtained by electrospinning technique, and morphological, thermal, mechanical and surface properties were characterized. The incorporation of AMX seemed to alter the nHAp distribution within the microfibrous matrix. The interaction between AMX and nHAp affected the mechanical performance and modulated the antibiotic release behavior. AMX release profiles presented a burst release that depended on nHAp content, followed by a slow release stage where the drug content (85–100%) was released in 3 weeks. The antimicrobial activity of the AMX‐loaded membranes was tested with four bacterial strains depended on both the drug and nHAp contents. Extensive mineralization in simulated body fluid (SBF) was evidenced by SEM/EDX analysis after 21 days. The studied electrospun nanocomposite amoxicillin‐loaded membranes could be a promising fibrous‐based antibiotic carrier system for dental and tissue engineering applications. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 966–976, 2017.